KORELASIONAL ANTARA SOSIAL-EKONOMI, HUKUM DAN MANAJEMEN DENGAN KUALITAS HUTAN MANGROVE DI KABUPATEN PEMALANG - Sri Puryono KS (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
The roles of mangrove forest both physic and biologic can not changed by other ecosystem. On the other side, the condition of mangrove forest is in critical damage now. Many factors that caused the damage of mangrove forest have been studied. This research was to know the dominant factors that influence to quality of mangrove forest by describing social economy correlation, law and management. Qualities of social-economy, law and management both separate and together most has relation with quality of mangrove forest. The social-economy variable show that there is strongly correlation to quality of mangrove forest (R = 0,615), law variable (R= 0,727) and management variable (0,820). While as together the three of those variables have strongly correlation (R= 0,927) to quality of mangrove forest.